Mass cytometry identifies characteristic immune cell subsets in bronchoalveolar lavage fluid from interstitial lung diseases - Hata, Kentaro; Yanagihara, Toyoshi; Matsubara, Keisuke; Kunimura, Kazufumi; Suzuki, Kunihiro; Tsubouchi, Kazuya; Eto, Daisuke; Ando, Hiroyuki; Uehara, Maki; Ikegame, Satoshi; Baba, Yoshihiro; Fukui, Yoshinori; et al. (Frontiers in Immunology, 2023)
Immune cells have been implicated in interstitial lung diseases (ILDs), although their phenotypes and effector mechanisms remain poorly understood. To better understand these cells, we conducted an exploratory mass cytometry analysis of immune cell subsets in bronchoalveolar lavage fluid (BALF) from patients with idiopathic pulmonary fibrosis (IPF), connective-tissue disease (CTD)-related ILD, and sarcoidosis, using two panels including 64 markers. Among myeloid cells, we observed the expansion of CD14+ CD36hi CD84hi monocyte populations in IPF. These CD14+ CD36hi CD84hi subsets were also increased in ILDs with a progressive phenotype, particularly in a case of acute exacerbation (AEx) of IPF. Analysis of B cells revealed the presence of cells at various stages of differentiation in BALF, with a higher percentage of IgG memory B cells in CTD-ILDs and a trend toward more FCRL5+ B cells. These FCRL5+ B cells were also present in the patient with AEx-IPF and sarcoidosis with advanced lung lesions. Among T cells, we found increased levels of IL-2R+ TIGIT+ LAG3+ CD4+ T cells in IPF, increased levels of CXCR3+ CD226+ CD4+ T cells in sarcoidosis, and increased levels of PD1+ TIGIT+ CD57+ CD8+ T cells in CTD-ILDs. Together, these findings underscore the diverse immunopathogenesis of ILDs.